2018
DOI: 10.1021/acsami.8b07570
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Triggered Nanoscale Metal–Organic Frameworks for Enhanced Anticancer Activity

Abstract: The oxygen-dependent feature of most photosensitizers (PSs) and the aggravated hypoxia tumor microenvironment seriously impede the photodynamic therapy (PDT) effectiveness. However, this undesirable impediment can be utilized to further trigger the activation of hypoxia-sensitive prodrugs. Moreover, a combined therapy can be used by associating PDT with hypoxia-activated chemotherapy. Herein, a multifunctional Hf-porphyrin nanoscale metal-organic framework (NMOF) platform [Hf/tetra(4-carboxyphenyl)porphine (TC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 61 publications
2
74
0
Order By: Relevance
“…A similar study based on Hf‐TCPP, TPZ, and dopamine‐derived polymer (DOPA‐PIMA‐mPEG) was also reported by Xie et al. in 2018 …”
Section: Targeted Strategiessupporting
confidence: 71%
“…A similar study based on Hf‐TCPP, TPZ, and dopamine‐derived polymer (DOPA‐PIMA‐mPEG) was also reported by Xie et al. in 2018 …”
Section: Targeted Strategiessupporting
confidence: 71%
“…The strategy for the synthesis of the function‐adaptive MMNPs was shown in Scheme A. Hf (IV)‐based porphyrin MOFs were first synthesized by a simple solvothermal method according to previous studies . Then a facile ultrasonication treatment was employed to prepare the ultrasmall‐sized pMOF dots.…”
Section: Resultsmentioning
confidence: 99%
“…86 The realization of combination therapy based on NMOFs relied heavily on their multimodal loading capability. Recently, various types of therapeutic combinations, such as dual chemotherapy drugs, 69 chemotherapy/siRNAs, 68,77 chemotherapy/PDT, 27,32 PDT/ immunotherapy [87][88][89][90] or RT/immunotherapy 91,92 based on NMOFs have been examined for tumor therapies both in vitro and in vivo ( Table 3).…”
Section: Implication Of Nmofs In Combination Cancer Therapymentioning
confidence: 99%
“…Several studies demonstrated that combining chemotherapy based on PDT potentially enhanced anticancer efficacy. 27,95 The main obstacle of PDT is the hypoxia of tumor environment, which significantly limits its application. Therefore, relieving tissue hypoxia by NMOFs can be used to enhance the efficacy of PDT.…”
Section: Chemotherapy/pdt or Chemotherapy/ Pttmentioning
confidence: 99%
See 1 more Smart Citation